The RETRACTED: Influence of Leadership Style, Work Discipline and Non-Physical Work Environment on the Performance Employee - Dita Alma Novianti; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aimed to analyze how much influence leadership style, work discipline, and non-physical work environment influence employee performance. This research was conducted in BULOG Center South Jakarta. Data was taken by distributing questionnaires. Data processing using descriptive and inferential analysis using SPSS statistical tools 17. The sampling technique uses the formula Slovin. Based on data management by using descriptive analysis of the results obtained following regression equation Y = 10 172 + 0.268 X1 + 0.147 X2 + 0.254 X3. The results showed leadership style (X1), Work Discipline (X2), and Working Environment Non-Physical (X3) indicate the value of the coefficient of determination (R2) of 0.311, suggesting that the contribution of leadership style, work discipline, and non-physical work environment on employee performance of 31.1%. Based on these results there is a significant and positive influence. While the rest were influenced by other factors not examined. The benefits of this research are that it is useful for educational institutions, the public, or other companies who require information about the results of research on leadership style, work discipline, and non-physical work environment that affect the performance of employees at BULOG Center, South Jakarta. And can improve employee performance to be better than before.